"Together We Have Power": Personal Traumas and Political Responses among Activist Oaxaqueñas. (January 2014) - Talcott, Molly
Activist Oaxacan women's lived experiences of trauma and violence have shaped their participation in indigenous-led anti-neoliberal organizing. The multifaceted dimensions of violence they experience–which are at once deeply structural and personal—have produced an intimate, embodied form of oppositional consciousness among them. The traumas of daily life are simultaneously racialized, gendered, and classed, and these embodied experiences can, and sometimes do, produce political responses among women. As they engage in activism that challenges capitalist incursions in the countryside, they are able to link the various traumas they face and, in so doing, become more effective protagonists in their interconnected journeys toward personal and structural emancipation. Experiencias vividas por mujeres militantes de Oaxaca del trauma y la violencia han dado forma a su participación en la organización anti-neoliberal liderada por las indígenas. Las dimensiones multifacéticas de violencia que sufren, que son a la vez estructurales y profundamente personal, han producido una forma íntima y encarnada de conciencia de oposición entre ellas. Los traumas de la vida cotidiana son al mismo tiempo racializados, de género, y de clase, y estas experiencias encarnadas pueden, y a veces lo hacen, producir respuestas políticas entre las mujeres. Al participar en el activismo que desafía las incursiones capitalistas en el campo, ellas son capaces de vincular los diversos traumas que enfrentan y, al hacerlo, se convierten en protagonistas más efectivas en sus pasos interconectados hacia la emancipación personal y estructural.